1984
DOI: 10.1016/0014-5793(84)81298-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and partial DNA sequence of the gene for the α‐subunit of the ATP synthase complex of Chlamydomonas reinhardii chloroplasts

Abstract: The partial DNA sequences of two unidentified genes flanking the gene for the large subunit of ribulose bisphosphate carboxylase of Chlamydomonas reinhardii have been reported [(1982) J. Mol. Biol. 162, 775-7931. Based on a comparison of the derived amino acid sequence of one of these genes with the corresponding sequences from Nicotiana tabacum chloroplast DNA and the E. coli atp (unc) operon, one Chlamydomonas gene is identified as coding for the a-subunit of the ATP synthase complex. ChlamydomonasChloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The results are shown in Figures 4 and 5. We observed that the 2.2-kb transcript, which corresponds to the a subunit mRNA (Hallick, 1984), was present in similar amounts in mutant thm24 and in the wild type ( Figure 4A). The afpA transcript was also present in mutant F54 ( Figure 4A).…”
Section: Rates Of Synthesis Of the A And P Subunits In The Wild-type mentioning
confidence: 69%
See 1 more Smart Citation
“…The results are shown in Figures 4 and 5. We observed that the 2.2-kb transcript, which corresponds to the a subunit mRNA (Hallick, 1984), was present in similar amounts in mutant thm24 and in the wild type ( Figure 4A). The afpA transcript was also present in mutant F54 ( Figure 4A).…”
Section: Rates Of Synthesis Of the A And P Subunits In The Wild-type mentioning
confidence: 69%
“…Plasmids carrying chloroplast DNA fragments with atpA, atpB, and psbA sequences were kindly provided by J. D. Rochaix (University of Geneva, Geneva, Switzerland). The atpA probe was a part of the R7 chloroplast DNA fragment according to the nomenclature of Rochaix (1978): the 0.9-kb EcoRI-Pstl fragment was interna1 to the coding sequence of the atpA gene (Dron et al, 1982;Hallick, 1984). The atpB probe was the 2.9-kb EcoRI-Kpnl fragment (containing the atpB gene) of the Ba5 chloroplast DNA fragment (Woessner et al, 1986).…”
Section: Rna Lsolation and Fina Gel Blot Analysismentioning
confidence: 99%
“…Introns are drawn in thinner lines relative to the coding sequences. Dark ~edgcs indicate 12 identified tRNA genes of which three are located within the inverted rcpcat [53] (scc Table 2 [22], atpA [23], atpB [24,25] atpE. atpF, atptt (J. Woessncr, J. Robertson, J. Boynton and N. Gillham, unpublished rcsuhs), rhcL [19], tufa [26], rpoA [27], q~oB, q~oC, dnuA [28] (S. Surzvcki, unpublished results) q~s-12, rps-7, rpl-2 [50].…”
Section: 2mentioning
confidence: 99%
“…Recently the molecular structure at 0.3 nm resolution of the reaction center of Rhodopseudomonas viridis has been determined by X-ray diffraction studies on crystallized reaction centers [85]. Based on the 23 structural and functional homology between the two bacterial and PSII subunits, it has been proposed that D2 and D1 are the apoproteins of the stable primary and secondary electron acceptors of PSII, respectively, and that they can be folded with 5 transmembrane domains to form a core with chlorophyll, pheophytin and quinone which is very similar to the bacterial reaction center [82,85]. While this model of D1 (Fig.…”
Section: Photosystem H (Psii)mentioning
confidence: 99%
“…The DNA sequencing studies on the atpA (4,10), atpB (28), and the atpE (this paper) genes of C. reinhardtii reveal that the coding regions exhibit different degrees of conservation with respect to the same genes from higher plant chloroplasts; the atpB gene the most conserved and the atpE gene the least conserved. However, the organization of the six ATPase genes in the C. reinhardtii chloroplast genome has diverged tremendously from that found in higher plant genomes.…”
Section: Introductionmentioning
confidence: 99%